2011
DOI: 10.1002/app.34633
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of linear low‐density polyethylene/sepiolite nanocomposites

Abstract: Linear low-density polyethylene (LLDPE)/ sepiolite nanocomposites were prepared by melt blending using unmodified and silane-modified sepiolite. Two methods were used to modify sepiolite: modification before heat mixing (ex situ) and modification during heat mixing (in situ). The X-ray diffraction results showed that the position of the main peak of sepiolite remained unchanged during modification step. Infrared spectra showed new peaks confirming the development of new bonds in modified sepiolite and nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…It has been reported that this stepwise mass loss in sepiolite is due to the loss of adsorbed and zeolitic water, the loss of rst and second structural water and the release of water through dehydroxylation. 24 It was observed that the thermal stability of composites is higher than that of pristine HDPE (Fig. 10a).…”
Section: Thermogravimetric Analysismentioning
confidence: 92%
“…It has been reported that this stepwise mass loss in sepiolite is due to the loss of adsorbed and zeolitic water, the loss of rst and second structural water and the release of water through dehydroxylation. 24 It was observed that the thermal stability of composites is higher than that of pristine HDPE (Fig. 10a).…”
Section: Thermogravimetric Analysismentioning
confidence: 92%
“…Among nanofillers, sepiolite is a low cost acicular shape clay nanoparticle with high specific surface area and excellent sorption properties, good mechanical strength and thermal stability, offering an ideal reinforcement for polymer matrices. Thus, PE ‐ sepiolite nanocomposites are very interesting materials because they can combine the excellent mechanical properties of this polymer with the high sorption capacity of sepiolite for developing textile fibers with higher absorbency and odor neutralization . Moreover, in the specific case of clay nanoparticles, the modification of barrier properties, water absorption and the biocide activity of the material can be also achieved .…”
Section: Introductionmentioning
confidence: 99%
“…(4) Increased surface area for chemical attack. 18,19 In this work, three approaches were simultaneously used to improve the thermal, mechanical and rheological behavior of linear low-density polyethylene (LLDPE)/starch/sepiolite composite. The only drawback of such biodegradable composites is the compatibility of its constituents.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It has also been used in small quantity to improve the mechanical properties of polymers. 18,19 In this work, three approaches were simultaneously used to improve the thermal, mechanical and rheological behavior of linear low-density polyethylene (LLDPE)/starch/sepiolite composite. First, the materials were prepared by peroxide initiated melt mixing technique, which avoids the use of organic solvent.…”
Section: Introductionmentioning
confidence: 99%